Tata Kelola Rekam Medis Berbasis Elektronik dalam Pelepasan Informasi Rekam Medis dengan Menggunakan Metode Agile - Safitri, Siti Aisah Nuraini; Syahidin, Yuda; Yunengsih, Yuyun (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2023)
The implementation of information release in medical summary requests at Arcamanik Hospital Bandung currently does not implement an electronic-based medical record management system so that the handling of information requests becomes inefficient, and increases the risk of security and privacy of patient data. Therefore, this study aims to implement electronic-based medical record governance in the release of medical record information using the agile method. The agile method is used as an option to solve problems in improving the medical record management system, this method provides flexibility and adaptability in system design, so that it can adjust to user requests. Agile stages include system requirements analysis, design, coding and black box testing. Data was collected through field studies and literature studies related to the implementation of electronic medical record governance. As a result, applying the agile method in this study can help and be an effective solution to improve the quality of medical record management, optimize the handling of information requests, increase the accuracy and security of information, and increase user satisfaction, so that the implementation of electronic-based medical record governance with the agile method can be used as an alternative for health agencies in managing medical records.